A Comparative Study of Ayurveda and Siddha System of Medicine - Guguloth, Ramesh; C. R., Yadav; Vasam, Dr. Kashaiah (International Journal of Innovative Research in Medical Science, 2017)
Ayurveda and Siddha systems of medicine have taken their origin from the Vedic and post-Vedic medical wisdom. Initially both were united and gradually they included sight different angle of approach in treatment and is being practised separately for the last 1,500 years. Siddha has been mainly popular in Tamil Nadu and Kerala in comparison to nationwide popularity of Ayurveda. Though from various aspects both seem to be different systems but owing to their same origin they have sample number of similarities. Scientific and rational analysis of similarities and dissimilarities between the two systems is the main focus of this review.